"Is it possible that there will be a water shortage in Uzbekistan by 2030?" (Texas Journal of Engineering and Technology, 2023)
In this article, MHTI experts studied how the water shortage in Uzbekistan affects the agricultural sector of arid regions. By 2030, there may be a shortage of 7 billion cubic meters of water in the country. As a result, there is a possibility that Uzbekistan will fall into the ranks of 33 countries with water shortages. The experts of the Institute of Macroeconomic and Territorial Research (MHTI) have analyzed the impact of water shortage in Uzbekistan on the agricultural sector of arid regions. have been studied and given data.